A Cross-sectional Observational Study of Noninfectious Dermatoses in Geriatric Population - Prachi Singh Rajpoot; Sheetal Poojary; Hari Pathave (Wolters Kluwer Medknow Publications, 2024)
Introduction: The geriatric population is expected to constitute 21.1% of total population in India by 2051. Geriatric population is associated with increased prevalence of various chronic diseases, physical disabilities, mental illness, and comorbidities. The trend is changing towards dermatoses of noninfective etiology owing to factors such as increased literacy rates and hygienic practices. Thus, our study is to focus on pattern of dermatoses of noninfective etiology in the most neglected yet important section of our population, that is, geriatric population. Objective: The objective of this study was to measure the prevalence of various noninfectious dermatoses among geriatric patients attending the skin outpatient department (OPD) at a tertiary care center. Methods: Two hundred and seventy-seven geriatric patients visiting skin OPD at a tertiary care center presenting with various noninfectious dermatoses were included, and the prevalence of various noninfectious dermatoses in this section of population was studied. Results: Eczemas were the most common group of noninfectious dermatoses (29.6%), followed by papulosquamous disorders (20.6%). Simultaneously associated systemic diseases and physiological changes were studied. Out of 277 patients, 156 (56.3%) had associated systemic illness. Eighty-seven (31.4%) patients were hypertensive, followed by diabetes mellitus (18.4%). The most common physiological change observed was wrinkling (47.6%), followed by seborrheic keratosis (46.2%). The Dermatology Life Quality Index (DLQI) score between 2 and 5, i.e., small effect on a patient's life, was significant in 100 (36.1%) patients, followed by moderate (DLQI 6-10 score), no effect (DLQI 0-1), very large (DLQI 11-20 score), and extremely large (DLQI 21-30) in 70 (25.3%), 57 (20.6%), 30 (10.8%), and 20 (7.2%) patients, respectively. Conclusion: In our study, eczemas were the most common group of noninfectious dermatoses in the elderly. So, simple measures such as diligent use of moisturizers, avoidance of harsh soaps and detergents along with adequate bathing time can decrease its prevalence.